2018
DOI: 10.1111/tmi.13082
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical characteristics of CMV coinfection among HIV infected individuals in Guinea‐Bissau: a cross‐sectional study

Abstract: CMV coinfection was detected among all enrolled patients and CMV viraemia was highly prevalent. Only age and upper gastrointestinal complaints were associated with the patients' CMV status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…CMV retinitis was detected at a lower level, between 0 and 2.6%. In the study, CMV viremia was found to be correlated with a significantly lower CD4+ cell count and an increase in activated and apoptosis-sensitive T lymphocytes [26,27]. Zhao et al found the overall positivity rate of CMV infection to be 29.5% in 808 HIV/AIDS patients and emphasized that a low CD4 T lymphocyte count and high HIV-1 viral load may be risk factors in these patients [28].…”
Section: Discussionmentioning
confidence: 88%
“…CMV retinitis was detected at a lower level, between 0 and 2.6%. In the study, CMV viremia was found to be correlated with a significantly lower CD4+ cell count and an increase in activated and apoptosis-sensitive T lymphocytes [26,27]. Zhao et al found the overall positivity rate of CMV infection to be 29.5% in 808 HIV/AIDS patients and emphasized that a low CD4 T lymphocyte count and high HIV-1 viral load may be risk factors in these patients [28].…”
Section: Discussionmentioning
confidence: 88%
“…CD28 − CD57 + CD8 + T-cells are believed to approach end-stage senescence [ 46 ]. Moreover, in general, nearly all HIV-infected people are also infected with cytomegalovirus (CMV) [ 47 , 48 ]. Several studies demonstrated that a persistent CMV infection, possibly acquired prior to HIV, also plays a substantial role in accelerating immunosenescence [ 47 , 49 ].…”
Section: Discussionmentioning
confidence: 99%